The efforts of Sheikh Muhammad al-Khal to prepare the first Kurdish-Kurdish dictionary - Tahir, Prof. Dr. Shahab Sheikh Taib; Abubakr, Asst. L. Rojan Qadir (Sulaimani Journal for Humanities, 2023)
The research is entitled (The efforts of Sheikh Muhammad al-Khal to prepare the first Kurdish-Kurdish dictionary), in which those efforts were discussed and how the dictionary was developed by Sheikh Muhammad al-Khal and how he dealt with the information that should be included in the dictionary entries, and that he made tremendous efforts for nearly forty years to compile this dictionary. He named it as (Fahrahhangi Khal / Dictionary of Al-Khal), the first part was printed in 1960, the second in 1964, and the third in 1976. It was printed several times and in different forms, as the three parts were collected and printed separately. The lexicographer Sheikh Muhammad Al-Khal tried to give the fruit of his efforts to his nation and bring the dialects closer together through his use of the words and vocabulary of all those dialects in his dictionary. Given the importance of this dictionary, we decided to devote our research to studying this dictionary in a linguistic-lexical study and to touch on the positive and negative points in it. For this reason, we divided the research into two chapters: -The first chapter: was devoted to introducing the dictionary and previous works written about this dictionary. - The second chapter: was devoted to studying the dictionary from a linguistic standpoint, in which we discussed this dictionary in terms of: (terminology, his skills for explaining vocabulary, and in return his lack of interest in some terms and words, morphological and grammatical information, lexical entries and explaining them and giving linguistic information to those entries, interest in proverbs and expressions Conventional (idium -idiom) ...etc. At the end of the research, we reached several points of results, and we mentioned the sources that were used to write the research, and then we concluded the research with a summary in Arabic and English.